2020
DOI: 10.1002/jgh3.12450
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for Parkinson's disease: Current evidence and future directions

Abstract: The gut–brain axis is a hot topic in Parkinson's disease (PD). It has been postulated that gut pathogens and dysbiosis can contribute to peripheral inflammatory states or trigger downstream metabolic effects that exacerbate the neurodegenerative process in PD. Several preclinical and clinical studies have demonstrated disrupted intestinal permeability, intestinal inflammation, altered gut microbiome, and reduced fecal short‐chain fatty acids in PD. In this regard, microbial‐directed therapies such as probiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 74 publications
(176 reference statements)
0
41
0
Order By: Relevance
“…The most powerful vehicle used in clinical practice to diminish PD-related symptomatology and the associated comorbidities causative or not are probiotics [13]. These are live microorganisms known to have a helpful role in improving digestive function [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The most powerful vehicle used in clinical practice to diminish PD-related symptomatology and the associated comorbidities causative or not are probiotics [13]. These are live microorganisms known to have a helpful role in improving digestive function [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of JGH Open , Tan et al . have summarized some of the current evidence for the role of probiotics in PD 6 . They reported that probiotics not only led to a reduction in neurotoxic metabolites but was able to improve motor function in studies conducted on mouse models of PD.…”
mentioning
confidence: 99%
“…Constipation is extremely common, causing significant distress to patients with PD, and is notoriously resistant to current laxatives 7 . Two randomized controlled trials have demonstrated the superiority of multistrain probiotics over placebo in improving constipation in PD over a 4‐week period 6 …”
mentioning
confidence: 99%
See 2 more Smart Citations